A New Formulation for Optimising Coal Procurement in Power Generation - Ibrahim, Jafni Azhan (2014)
Coal consumption has accounted for about 40% of fuel used in the world power generation activities. The significant increase in coal-fired electricity generation in developing countries (i.e. China and India) has further positioned coal as an important fuel in power generation. In this industry, the volatility of coal price in recent years has put tremendous pressure for power producers to minimise their fuel cost since it makes up a large portion of cost in power plant operations. At the same time, continuous supply of coal is also vital to ensure electricity generation system’s security in which possible interruptions like weather inclement, volatility in coal freight market, logistic infrastructures and political interventions in key coal producing countries have been persistently dominating the industry. Thus, moderating the issues of cost and supply security has become a mounting challenge to all entities involved. In addressing this issue, this paper explores an alternative to develop a new formula to select an optimal level of Total Exposure (TE) in coal procurement for power generation which meets both acceptable financial cost (Cost of Procurement, CoP) and security risk requirement (Risk of Procurement, RoP). Firstly, in determining the RoP, this paper takes into consideration the relationship between Non-delivery Probability Table (NdPT) and Supply Shortage Impact (SSI) and quantifies the RoP in monetary terms. The NdPT illustrates the probability of shortage from a particular procurement portfolio, whilst the SSI reflects the cost of shortages. Then, CoP is introduced to determine the cost of coal supply by means of multiplying selected suppliers’ prices with quantities allocated to them. Finally, the new optimisation formula will reflect a unique combination between CoP and RoP that yields minimum TE. The system is then deemed optimised as it balances both, the level of risk and the cost.